Leading beyond sustainability in Nigerian higher education institutions: imperatives for quality management and technology acceptance - Ayodele, Lasisi Abass; Mohd Ali, Hairuddin; Usman, Shuaibu Hassan (iSTEAMS Research Nexus 2013, 2013)
Leadership is a protruding aspect that needs enquiry based on the extent to which administration practices in higher education institutions (HEI) to achieve quality. The main argument of this paper emanates from the understanding that “quality management in HEI” is a highly challenged aspect that requires “strategies” and should follow basic approach of quality assurance, quality control, strategic planning and technology acceptance in managing educational institutions for quality achievement and sustainability of HEI. The quality management theory not unturned any stone in order to provide quality service and leading beyond through technology acceptance to catch new customers for high achievement. Thus, the study is seizure method of administrating and application of technology in carrying out quality services in educational institutions.